The Understanding of Ascesis in Christianity - Platovnjak, Ivan; Prijatelj, Erika; Zovko, Vinko (Studia Gdańskie, 2023)
Just as all the world's religions know ascesis, so does Christianity. This fact raises different questions: Is ascesis the same in Christianity as in other religions? How do Christians understand ascesis? Can we say that there is a Christian ascesis? In this article the authors try to answer these questions. First, they briefly define the term ascesis, and then they outline the biblical foundations of ascesis and its history. Then they show how Christians understand ascesis and in what sense it is Christian ascesis, and its various forms. Finally, they show the criteria of discernment that must be observed in order for ascesis to be authentically Christian and to enable one to live freedom in Christ and the fullness of life in the love of God the Father through Jesus Christ in the Holy Spirit.